Insightful quality beyond continuous improvement - Sower, Victor E.; Fair, Frank ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2012)
Warren Bennis said that management is about doing things right while leadership is about doing the right things. Of course organizations need both good management and good leadership--they need to do the right things right, but Bennis contended that modern organizations are often under-led and over-managed. It is organizational leadership that is essential to attaining and maintaining market leadership over time, and accomplishing this cannot be done with simple solutions or silver bullets. Continuous improvement--optimizing processes, reducing costs, eliminating defects--is about doing things right and is vital to an organization's success. But incremental improvement alone will not assure the long-term success of the organization. Being the low-cost producer of the world's best 1960s era slide rule will not enable a company to compete in today's electronic calculator, tablet computer, and PC world. The world's best floppy disk cannot compete with today's low end USB flash drives--and new ferroelectric material-based memory devices currently under development promise to render flash drive technology obsolete. Today's consumers are not interested in purchasing slide rules and floppy disks even if they are inexpensive and 100% defect-free. Those are products of an obsolete paradigm, and in many cases the companies that produced them are no longer in existence.
List of tables -- List of figures -- List of examples -- Abbreviations and acronyms -- Acknowledgments -- 1. Introduction -- 2. Why continuous incremental improvement is not sufficient for organizational success -- 3. Insight -- 4. The insightful organization -- 5. Insightful ways of thinking for managers -- 6. Insightful use of existing tools -- Notes -- References -- Index.
Part of: 2012 digital library.
Includes bibliographical references (p. 107-117) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF t.p. (viewed on May 31, 2012).
Keywords: Organizational change; Leadership; Strategic planning; Insight; strategic quality management; breakthrough improvement; paradigm shift; continuous improvement; Plato; innovation; creativity; quality; technological forecasting; environmental scanning; benchmarking; house of quality; change management